ADMINISTRATION OF TRIGONA POLLEN ON ENDOMETRIAL THICKNESS IN WHITE MICE EXPOSED TO CIGARETTE SMOKE - Amira, Nurul; Laksmi, Desak Nyoman Dewi Indira; Setiasih, Ni Luh Eka (Buletin Veteriner Udayana, 2022)
Cigarette smoke is a source of free radicals. Inhaled cigarette smoke can cause disturbances in the reproductive organs, one of which is a disorder in the endometrium. The effect of free radicals from cigarette smoke on the endometrium can be reduced by giving antioxidants. One source of antioxidants that is widely consumed by the public at this time is bee pollen trigona. In general, bee pollen trigona contains many nutrients, antioxidants and phytoestrogens that are very beneficial for the body. This study was experimental in a completely randomized design using 18 white rats (Rattus norvegicus) which were divided into 1 control group and 2 treatment groups. The control group (P0) was only exposed to cigarette smoke, treatment 1 (P1) was exposed to cigarette smoke and given 9 mg of bee pollen trigona, and treatment 2 (P2) rats were exposed to cigarette smoke and given 18 mg of bee pollen trigona. The treatment was carried out for 14 days with an adaptation period of 7 days previously. After 14 days, vaginal swabs were carried out on all rats to determine the period of estrus, if found rats in estrus, the rats were immediately sacrificed for uterine samples and histological preparations were made with Hematoxylin-Eosin staining. The variable examined was the thickness of the endometrium. Data analysis was carried out by testing the homogeneity of the data, then continued with the Analysis of Variance (ANOVA) test and the Games-Howell test. The results of this study indicate that there is a significant difference (P<0.05) at P0, P1, and P2. From the data analysis, it can be concluded that the administration of bee pollen trigona can increase the thickness of the endometrium in white rats.